Efficient electrochemical detection of cancer cells on in situ surface-functionalized MoS2 nanosheets. Issue 28 (26th June 2017) - Guo, Yulin; Shu, Yijin; Li, Aiqun; Li, Baole; Pi, Jiang; Cai, Jiye; Cai, Huai-hong; Gao, Qingsheng
Abstract : In situ surface functionalization by reactant molecules (thiourea) is feasible to engineer MoS2 surfaces with rich amino groups, leading to facile antigen immobilization and thus selective recognition of cancer cells. Abstract : Surface engineering is crucial to improve the biocompatibility and sensing response of two-dimensional (2D) nanomaterials. For nanostructured MoS2 biosensors, post functionalization via cumbersome procedures unfortunately leads to inevitable structural damage and thus reduced functionalities. Herein, in situ surface functionalization by the reactant thiourea (TU) was employed to one-step fabricate TU-capped MoS2 (TU-MoS2 ) nanosheets. The amino-group terminated surface of TU-MoS2 favours immobilization of the GE11 peptide that can specifically recognize cancer cells. The resulting sensor shows high sensitivity and selectivity in detecting cancer cells, relying on the varied expression of the epidermal growth factor receptor (EGFR) on cell membranes. In the case of human liver cancer cells, it is featured by a wide linear range (50–10 6 cells mL −1 ) and a low detection limit (50 cells mL −1 ) in electrochemical impedance spectroscopy, as the variation of charge-transfer resistance is plotted against cell concentration. Furthermore, it exhibits good efficiency in monitoring the dynamic variation of EGFR expression on living cells in response to drug treatment, which is promising for clinical diagnosis and drug screening in miniaturization. By elucidating an efficient biosensing platform on the basis of surface engineered MoS2 nanosheets, this work sheds some light on the development of biosensing technology and relevant materials.